Early Bronze Age of the steppe Urals and Western Kazakhstan: some results and research prospects - Khavansky Alexey I.; Bisembaev Arman A. (Поволжская археология)
The article presents the history of the study and current state of the issues of the Early Bronze Age in Western Kazakhstan. This period in Western Kazakhstan is represented by monuments of the Yamnaya cultural-historical community. Before the beginning of the XXI century Yamnaya sites in Western Kazakhstan were represented by “classical” complexes, studied in the middle of the XX century on the river Ilek, the border of the Southern Ural and Western Kazakhstan. These are Tamar-Utkul VII and Tamar-Utkul VIII, Izobilnoye I and Izobilnoye II burial grounds, separate burials in the Mamai and Kresty burial grounds. Since the beginning of the XXI century, the unique Kumsay I burial ground has been studied in the south of the Aktobe region. It consists of 168 barrows. There are from 1 to 5 burials in each barrow. The burial pose is crouched on the back and sitting. The bones are covered with ocher, both completely and partially. A characteristic feature is the unstable orientation of the buried skeletons. Along with the orientation to the eastern sector, characteristic of the Yamnaya cultural and historical community, at least half of the buried are oriented to the northern sector with deviations. New materials make it possible to raise questions about the southern border of the Yamnaya cultural-historical community, migration routes and cultural contacts of the population of this community.